Combination of Systemic Inflammation Response Index and Platelet-to-Lymphocyte Ratio as a Novel Prognostic Marker of Upper Tract Urothelial Carcinoma After Radical Nephroureterectomy - Zheng, Yangqin; Chen, Yuming; Chen, Jingfeng; Chen, Wu; Pan, Yue; Bao, Lianmin; Gao, Xiaomin (Frontiers in Oncology, 2019)
This study aimed to evaluate the preoperative prognostic value of systemic inflammation response index and platelet-to-lymphocyte ratio (SIRI-PLR) in patients with upper tract urothelial carcinoma (UTUC). The prognostic ability of SIRI-PLR was evaluated in a training cohort comprising 259 patients with UTUC who underwent radical nephroureterectomy and was further validated in an independent cohort comprising of 274 patients. Multivariate Cox regression models showed that SIRI was significantly associated with overall-survival (OS), cancer-specific survival (CSS), and metastatic-free survival (MFS), and PLR significantly affected OS and CSS (all P values < 0.05). In particular, a simultaneously high SIRI-PLR value was considered an independent risk factor even after adjusting for confounding factors and was superior to SIRI alone in predicting survival among patients with UTUC. The analyses of concordance-index and receiver operating characteristic curve showed that incorporation of SIRI-PLR versus without its incorporation into newly developed nomograms or currently available clinical parameters, such as pathologic T stage, N stage, or tumor grade, had higher accuracy in predicting urologic outcomes of patients with UTUC. These results were observed in the training cohort and were confirmed in the validation cohort. In conclusion, patients with a simultaneously high SIRI-PLR value had significantly poor prognosis. Incorporating SIRI-PLR into currently available clinical parameters can help in patient management.